Devil and the bluebird - Mason-Black, Jennifer (Amulet Books, 2016)
"Blue Riley has wrestled with demons ever since the loss of her mother to cancer. But when she encounters a beautiful devil at her town crossroads, it's her runaway sister's soul she fights to save. The devil steals Blue's voice-inherited from her musically gifted mother-in exchange for a single shot at finding Cass."--Book jacket.